RETINOBLASTOMA FAMILIAL IN A 3-YEAR-OLD GIRL - Wini Mardewi, Kadek; Ariawati, Ketut (Medicina, 2013)
Retinoblastoma is the commonest intraocular tumor in childhood. About one thirds  of all cases are bilateral. It is recognized that bilateral and familial retinoblastoma are cause by germline mutation and are thus a heritable tumor. We reported a case, 3-year-old girl showing proptosis of the right eye since six months before admission. She had family history (his father) of retinoblastoma. Physical examination showed mass of the righ eye and leucorea of the left eye. Computed tomography scan showed  retinoblastoma extraoccular of the right eye and retinoblastoma intraoccular of the left eye without spread to the pinealis gland or Parsellar. Bone marrow aspration showed non hemopoitic cell (metastatic tumor). Patient was diagnosed with bilateral retinoblastoma familial grade V. Despite the management of this patient is chemotherapy and still on treatment chemotherapy continuous phase, the prognosis still worse. [MEDICINA 2013;44:128-134]